The Regulatory Function of CCR9+ Dendritic Cells in Inflammation and Autoimmunity - Pathak, Manisha; Lal, Girdhari (Frontiers in Immunology, 2020)
Chemokine receptor CCR9 is a G protein-coupled receptor and express on several types of immune cells, including dendritic cells, CD4+ T cells, and B cells. CCR9 drives the migration of immune cells to gradients of its cognate ligand CCL25. The chemokine CCL25 is mostly produced by gut and thymic epithelial cells. Gut- and thymic-homing dendritic cells (DCs) are known to express CCR9, and these cells predominantly localized in the gut lining and thymus. CCR9+ DCs are implicated in regulating inflammation, food allergy, alloimmunity, and autoimmunity. Differential interaction of CCR9+ DCs with lymphoid and myeloid cells in the thymus, secondary lymphoid tissues, and mucosal sites offer crucial insights to immune regulation. In this review, we reviewed the phenotypes, distributions, and interactions of CCR9+ DCs with other immune cells, elucidating their functions and role in inflammation and autoimmunity.